Virus Persistence Of Mosaic Causes In Chili Seed At Different Temperatures: Persistensi Virus Penyebab Mosaik Pada Benih Cabai Pada Beberapa Suhu - Sopialena (Universitas Widya Gama Mahakam, 2020)
The study entitled Persistence of the virus that causes mosaic disease in chili seeds originating from the production of chili plants that are attacked by a virus that is treated by soaking at some temperature aims to see the persistence or presence of the virus that causes the mosaic. The persistence of the virus is done by observing the chilli seedlings that are 8 weeks after planting. The research was carried out at the Plant Pest and Disease Laboratory, Faculty of Agriculture, Mulawarman University, Samarinda. The study was conducted using the observation method that is directly observing the treatment carried out. This study used 5 treatments and each of 4 replications, consisting of: C1 = treatment of warm water with a temperature of 40 ° C for 10 minutes, C2 = treatment of warm water with a temperature of 45 ° C for 10 minutes, C3 = treatment of warm water with a temperature 50 ° C for 10 minutes, C4 = treatment of warm water with a temperature of 55 ° C for 10 minutes, Cs = treatment of warm water with a temperature of 60 ° C for 10 minutes. The results showed that soaking warm water had an influence on the persistence of viruses carried in the seeds to the development of mosaic disease in chilies. Temperatures of 50 ° C and above have been able to prevent mosaics disease at chillie plant.